Diverting blame to stay sane - young people’s strategies for dealing with the mental health effects of precarious employment: a grounded theory study - Toivanen, Susanna (BMC Public Health, 2020)
BACKGROUND: Precarious employment is a risk factor for poor mental health, particularly among young adults. Knowledge about how young people maintain their mental health while in a precarious employment situation is scarce. The aim of the study was to explore the meaning of precarious employment for young adults in Sweden and their strategies for maintaining good mental health. METHODS: In-depth interviews were conducted with 15 individuals (9 men and 6 women) aged 20–39 years in a precarious employment situation. Contact persons at union offices and at specific job-coaching organizations collaborating with the Swedish public employment agency in the city of Malmö were gate openers to reach informants. Analysis was based on constructivist grounded theory, implying an emergent design where data collection and analysis go hand in hand. RESULTS: All informants had completed secondary school in Sweden, and one third had studied at the university level. A majority currently had jobs; however, they were mostly employed on an hourly basis and only a few had temporary full-time jobs. The analysis resulted in a core category “Diverting blame to stay sane,” which summarized an emergent coping process involving individual resources and resources represented by the individuals’ social capital. The developed theoretical model contained four main categories, “Facing reality,” “Losing control,” “Adapting,” and “Fighting back,” related to the core category. CONCLUSIONS: The results implied a process where the challenges created by loss of employment-based rights required a coping process where the individual’s social capital plays an important role. However, social capital is to a large extent determined by contextual factors, underlining the strong health equity aspect of precarious employment.